PENINGKATAN LITERASI PEMBELAJARAN KOMPETENSI GAYA MELALUI PROBLEM BASED LEARNING BERBANTUAN FLASHCARD KELAS IV SDN JATISARI (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The background for writing this is that based on the results of observations in class IV SDN Jatisari found problems including low reading interest due to the lack of availability of varied teaching resources for students. Then the learning model is still conventional. To overcome these problems, teachers can use the Flashcard-assisted Problem Based Learning model which can attract and facilitate student understanding both visually and in writing. The purpose of writing this is to describe the design of learning literacy, test the improvement of processes and results and find out the impact of implementing Problem Based Learning assisted by Flashcard media for fourth grade students at SDN Jatisari. Data collection techniques using tests, observation and documentation. The results of the percentage of students' independent literacy abilities show an average score of 85.25% (good) and critical reasoning abilities show a score of 86% (very good). For Pretest and Posttest learning outcomes there is an average increase of 19. The conclusion of this best practice is the design of learning literacy using Problem Based Learning assisted by Flashcards. The application of the Problem Based Learning model assisted by Flashcards is effective for the literacy skills of fourth grade students at SDN Jatisari Semarang. besides that this has an impact on writers, students, teachers and schools.